Non-resolving long term Mucormycosis in Post-COVID-19 Patient: A Case Report - Bhattarai, Sanjeet; Karthak, Ashish; Gurung, Naresh; Shrestha, Ashish; Lama, Rakesh; Bhusal, Yuvaraj; Giri, Bijay; Chhetri, Sujan; Shrestha, Sanjeet Krishna (Nepalese Respiratory Journal, 2022)
With the second wave of COVID-19, there was a surge of cases of mucormycosis co-infection in our health center. We would like to present a case of a 53 years old man with COVID-19 positive status who later developed mucormycosis, with invasion of Maxillary sinus, jugular vein, digastric recess in MRI. He was managed with Amphotericin –B injection along with insulin therapy in sliding scale and Posaconazole thereafter for six months. Debridement of the lesion was done along with removal of inferior alveolar process of maxillary process and 3 molar teeth and a premolar tooth of upper left side.